To fight or fly: Law Brothers auto accessories - Salleh, Rosli; Law, Ai Ling; Ibrahim, Saadiatul (Universiti Putra Malaysia Press, 2014)
This case describes the stiff competition faced by Law Brothers, a pioneer in the car accessories industry. The negative financial result during the past few years had forced the company to struggle for possible solutions. The company had to consider alternative ways to grow the business, diversify or merge with the other players to remain relevant in the industry. This case is suitable for undergraduate and postgraduate courses in strategic management, entrepreneurship and marketing.